Digital Reflective Teaching-Based English Teacher Professional Development Management Model to Improve Students' Pedagogical Competence and Critical Literacy - Yuliana, Elis; Haryati, Sri; Sukarno, Sukarno; Muhlisin, Ahmad (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The aim of this research is to develop and test a digital reflective teaching-based English teacher professional development management model to improve students' pedagogical competence and critical literacy. Method: The research method uses research and development (R&D) through five stages, namely preliminary study, model design, expert validation, testing at SMP Negeri 13 Magelang, and model revision. Data were obtained through focus group discussions with education experts and practitioners, as well as field experiments using a nonequivalent control group design. Qualitative analysis was performed on the FGD results, while quantitative data were analyzed using ANCOVA and N-Gain tests. Results: The results showed that the developed model included a cycle of competency reflection, performance assessment, self-development plan preparation, learning implementation, digital reflection (teachers, students, peers), and comprehensive evaluation that was repeated to support the improvement of teachers' pedagogical competencies. The implementation model in English subjects at SMP Negeri 13 Magelang has a significant influence on students' critical literacy (sig. 0.000). The average N-Gain score of the experimental class (0.60) was higher than that of the control class (0.38), with the greatest increase in the indicator of focusing on sociopolitical issues. These findings prove that the integration of digital reflective teaching not only strengthens the management of teachers' professional development but also has a positive impact on the quality of learning and the strengthening of students' critical literacy in the era of education 4.0.